Tryptophan metabolism drives dynamic immunosuppressive myeloid states in IDH-mutant gliomas - Friedrich, Mirco; Sankowski, Roman; Bunse, Lukas; Kilian, Michael; Green, Edward; Ramallo Guevara, Carina; Pusch, Stefan; Poschet, Gernot; Sanghvi, Khwab; Hahn, Markus; Bunse, Theresa; Münch, Philipp; et al. (Nature Cancer, 2021)
The dynamics and phenotypes of intratumoral myeloid cells during tumor progression are poorly understood. Here we define myeloid cellular states in gliomas by longitudinal single-cell profiling and demonstrate their strict control by the tumor genotype: in isocitrate dehydrogenase (IDH)-mutant tumors, differentiation of infiltrating myeloid cells is blocked, resulting in an immature phenotype. In late-stage gliomas, monocyte-derived macrophages drive tolerogenic alignment of the microenvironment, thus preventing T cell response. We define the IDH-dependent tumor education of infiltrating macrophages to be causally related to a complex re-orchestration of tryptophan metabolism, resulting in activation of the aryl hydrocarbon receptor. We further show that the altered metabolism of IDH-mutant gliomas maintains this axis in bystander cells and that pharmacological inhibition of tryptophan metabolism can reverse immunosuppression. In conclusion, we provide evidence of a glioma genotype-dependent intratumoral network of resident and recruited myeloid cells and identify tryptophan metabolism as a target for immunotherapy of IDH-mutant tumors.
CRIS-Team Scopus Importer:2023-09-13